Dari Candaan Menuju Perundungan: Penyuluhan Hukum sebagai Upaya Preventif Bullying pada Siswa MAS Darul Falah Ulumuddin - Suryani; Ahmad Tholib; Marzuki; Raudhatul Jannah; Tri Utami; Elmardlatillah; Faturahmi; Nanang Qosim (Cv. Kalimasada Group, 2026)
This study aims to analyze the implementation of anti-bullying legal counseling as a preventive effort to increase students’ awareness of bullying behavior at MAS Darul Falah Ulumuddin. The research employed an empirical juridical approach with a field research method. Data were collected through observation, interviews, documentation, and discussions during the counseling activities. The findings reveal that some students still perceive mocking, giving nicknames, humiliating, and excluding peers as normal jokes, without realizing that such actions constitute bullying with negative psychological and social impacts. The implementation of legal counseling through lectures, discussions, and interactive question-and-answer sessions proved effective in improving students’ understanding of the forms, impacts, and social consequences of bullying. This study concludes that legal counseling plays an important role as a preventive measure in developing students’ social awareness and supporting the creation of a safe, comfortable, and respectful school environment